Evaluating effectiveness of girdle-herbicide containment of below-ground spread of oak wilt (Bretziella fagacearum) - Dustin R. Bronson; Jed Meunier; Teresa R. Pearson; Kyoko Scanlon (Forest Ecology and Management, 2023)

Evaluating Regeneration in Heterobasidion Root Disease Infested Stands in the Lake States - Michael C Demchik; Monique L Sakalidis; Michael Hillstrom; Kyoko Scanlon; Trevor A Adams; Katherine R Minnix (Forest Science, 2020)
Heterobasidion root disease (HRD) infection is becoming increasingly common in red pine plantations of the Lake States. Although stump treatment can reduce rates of overland transmission, infested stands continue to experience expansion of mortality pockets. Natural regeneration into HRD mortality pockets can assist with revegetation. The objective of this study was to determine what tree species naturally regenerate in red pine plantations impacted by HRD in Wisconsin and Michigan. We visited 49 pockets (in 31 stands) in Wisconsin and Michigan that had existing confirmed HRD infections during the fall of 2017. We surveyed the regeneration in the pocket and measured the species and basal area of overstory trees 10 m from the expanding edge of the pocket. Overall, pockets were regenerating with desirable species, some of which are susceptible to HRD. Additionally, woody invasive species were present in 39 percent of the pockets. We expect these pockets to generally fill with desirable species of regeneration, although long-term successful regeneration by susceptible species such as pines may be limited.